Comparison of water quality between sites with and without cage culture in Batang Ai reservoir, Sarawak - Khoo, Yen Nee (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study was carried out in the months of October and November 2011, and April 2012 to assess the impact of cage culture activities on the water quality at Batang Ai Reservoir, Sarawak. Water quality parameters were recorded at 3 sampling stations which are S1 (cage culture area), S2 (area without cage culture), and S3 (unpolluted area of the reservoir) at five different depths (subsurface, 5 m, 10 m, 20 m, and 25 m). For nutrients, the range for ammonia was 0 to 0.83 mg/L, for nitrate 0.4 to 9.6 mg/L, for nitrite 0.004 to 0.115 mg/L, for orthophosphate 0 to 0.43 mg/L, and silica 0.030 to 9.583 mg/L. The concentrations of nutrients in April 2012 were significantly different compared to in October and November 2011 because it was raining season, fishes were harvested, and water level of the reservoir rose in April 2011. The range for BOD5 was from 1.73 to 19.75 mg/L, COD from 0 to 21 mg/L, TSS from 0.500 to 11.019 mg/L, and chlorophyll-a from 0.192 to 11.706 (µg/L). TSS was highest at station 3 for all three samplings but is still under acceptable level for freshwater aquaculture. Chlorophyll-a was higher in station 1 and station 3 compared to the concentration of chlorophyll-a in station 2. Primary productivity and exposure tests of juvenile fishes were conducted during November 2011 and April 2012. The net primary production was higher at cage culture area compared to area without cage culture. The dissolved nutrients from urea and waste from feed fertilized the water and promote primary productivity. All juvenile fishes survived at depth of 5 m, 6 m, 7 m, and 8 m, but 100 % morlity at the depth of 10 m. Dissolved oxygen was found to be the main cause of juveniles’ mortality. These results indicated that cage culture activities and water input from upstream affects water quality at the reservoir.